Identification and assessment of non-conventional yeasts in mixed fermentations for brewing bioflavored beer - Sampaolesi, Sofia (2023)
The increasing demand for more flavored and complex beers encourage theinvestigation of novel and non-conventional yeasts with the ability to provide acombination of bioflavoring and low ethanol yields. The present study identified 22yeasts isolated from different brewing sources, including the fermentation by-productsknown as yeast sludges, and characterized a selection of strains to find the moresuitable for the aforementioned aims. HPLC and GC-FID analysis of its brewingproducts were performed.The most promising results were obtained with the non-conventional yeasts Pichiakudriavzevii MBELGA61 and Meyerozyma guilliermondii MUS122. The former, isolatedfrom a Belgian wheat beer sludge, was capable of growing in wort (17.0 °Bx, 20 °C)with very low ethanol yields (1.19% v/v). Besides, upon mixed fermentations withSaccharomyces cerevisiae was suitable to produce volatile compounds such as ethylacetate, 2-phenyl ethanol and isoamyl alcohol, with characteristic fruity notes. M.guilliermondii MUS122, isolated from a golden ale beer sludge, partially attenuated thewort with low production of ethanol and biomass. In addition, provided some fruity andfloral nuances to the aroma profile of mixed fermentations with brewer´s yeast.The results suggest that these strains favor the development of more fruity-floweryaroma profiles in beers. Furthermore, they are suitable for use in mixed fermentationswith Saccharomyces brewer’s strains, although the ethanol level did not decreasesignificantly.